Communication, organizing and organization: An overview and introduction to the special issue - COOREN, Francois (Institutional Knowledge at Singapore Management University, 2011)
This paper provides an overview of previous work that has explored the processes and mechanisms by which communication constitutes organizing (as ongoing efforts at coordination and control of activity and knowledge) and organizations (as collective actors that are 'talked' into existence). We highlight differences between existing theories and analyses grounded in communication-as-constitutive (CCO) perspectives and describe six overarching premises for such perspectives; in so doing, we sharpen and bound the explanatory power of CCO perspectives for organization studies more generally. Building on these premises, we develop an agenda for further research, call for greater cross-fertilization between the communication and organization literatures, and illustrate ways in which communication-informed analyses have complemented and strengthened theories of the firm, organizational identity, sensemaking, and strategy as practice.